A Bibliometric Analysis of the Employability Skills Research Trends in Vocational Education - Maharbid, Allan Anugraha; Kustiawan, Iwan (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2022)
Employability skills are the skills needed to acquire, retain, and do a good job. Employability skills are essential in helping prepare students to increase competitiveness and work productivity. The world of work wants graduates to be competitive and technically competent with skills relevant to technological developments. This study aims to analyze research trends related to employability skills in vocational education. We use bibliometric analysis procedures on 1123 published articles in the Scopus database. The results of this study reveal citation, co-authorship, co-citation, and keyword analyses producing a pattern of research maps in vocational education. The findings identify publication trends, widely cited articles, contributing countries, productive journals, and obtain information for future research on employability skills